TINJAUAN YURIDIS TERHADAP KEWENANGAN KPK DALAM PENYIDIKAN DAN PENUNTUTAN TINDAK PIDANA KORUPSI - Muhammad Ilham; Syafruddin Kalo; Madiasa Ablisar; Muhammad Ekaputra (USU LAW JOURNAL, 2018)
Abstract The criminal act of corruption is an extraordinary crime so that Indonesia forms a KPK given a special task to eradicate corruption. After the KPK was formed, Indonesia had 3 (three) institutions tasked with eradicating corruption, namely the Police, the Attorney General's Office and the KPK. The authority of the Corruption Eradication Commission in conducting investigations and prosecutions of corruption crimes is different from other institutions so that this study discusses the authority of the Corruption Eradication Commission in conducting investigations and combating corruption. This study discusses 3 problem formulations, namely (1) the form of KPK's authority on investigating cases of corruption in law enforcement; (2) the form of KPK's prosecution authority in an effort to tackle criminal acts of corruption; (3) the efforts of the KPK in tackling corruption. The results of this study indicate that (1) the authority of the Corruption Eradication Commission on investigating corruption cases comes from the Criminal Procedure Code and Corruption Law where the Criminal Procedure Code is lex generalis and the Corruption Act is lex specialis and the Corruption Eradication Commission Law which is sub-specialist (2) the authority of the Corruption Eradication Commission against prosecution of criminal cases corruption comes from the KUHAP, the Corruption Act, the Prosecutor's Law and the KPK Law. In this case, the authority of the Criminal Procedure Code is lex generalis, the investigative authority in the Corruption Act is lex specialis compared to the Criminal Procedure Code, and the KPK Law is lex specialis compared to the Corruption Law; (c) Efforts to tackle criminal acts of corruption are carried out by the KPK by carrying out (a) prevention efforts; (b) Enforcement efforts in the form of investigation, investigation and prosecution of corruption committed by the KPK, coordination and supervision with the Police and the Attorney General's Office to conduct investigations, coordination and supervision with the Prosecutor's Office to prosecute corruption; (c) Efforts to monitor state administration. Keywords: Prosecutor's Office, Police, KPK, investigation, prosecution